Low-Dose Triple Antihypertensive Combination Therapy in Patients with Hypertension: A Randomized, Double-Blind, Phase II Study - Hong SJ; Sung KC; Lim SW; Kim SY; Kim W; Shin J; Park S; Kim HY; Rhee MY (Dove Medical Press, 2020)
Soon Jun Hong,1,* Ki-Chul Sung,2,* Sang-Wook Lim,3 Seok-Yeon Kim,4 Weon Kim,5 Jinho Shin,6 Sungha Park,7 Hae-Young Kim,8 Moo-Yong Rhee9,10 On behalf of MH_APOLLO to read: HM_APOLLO1Department of Cardiology, Cardiovascular Center, Korea University Anam Hospital, Korea University College of Medicine, Seoul, Republic of Korea; 2Department of Cardiology, Gangbuk Samsung Hospital, Sungkyunkwan University College of Medicine, Seoul, Republic of Korea; 3Cardiology Division, Cardiac Center, CHA Bundang Medical Center, CHA University, Seongnam, Republic of Korea; 4Department of Cardiology, Seoul Medical Center, Seoul, Republic of Korea; 5Department of Internal Medicine, Kyung Hee University Medical Center, Kyung Hee University, Seoul, Republic of Korea; 6Division of Cardiology, Department of Internal Medicine, Hanyang University College of Medicine, Seoul, Republic of Korea; 7Department of Cardiology, Severance Hospital, Yonsei University College of Medicine, Seoul, Republic of Korea; 8Department of Health Policy and Management, College of Health Science & Department of Health Care Science, Graduate School, Korea University, Seoul, Republic of Korea; 9Cardiovascular Center, Dongguk University Ilsan Hospital, Goyang-si, Gyeonggi, Republic of Korea; 10College of Medicine, Dongguk University, Gyeongju-si, Gyeongbuk, Republic of Korea*These authors contributed equally to this workCorrespondence: Moo-Yong RheeCardiovascular Center, Dongguk University Ilsan Hospital, 27 Dongguk-Ro, Ilsandong-Gu, Goyang-si, Gyeonggi-do 10326, Republic of KoreaTel +82 31 961 5775Fax +82 31 961 7786Email mooyong_rhee@dumc.or.krPurpose: We evaluated the dose-responsiveness, efficacy, and safety of low-dose triple antihypertensive combination therapies in patients with mild-to-moderate hypertension.Patients and Methods: After a 1 to 2-week placebo run-in period, 248 patients were randomized to the half-dose triple combination (amlodipine 2.5 mg + losartan 25 mg + chlorthalidone 6.25 mg), third-dose triple combination (amlodipine 1.67 mg + losartan 16.67 mg + chlorthalidone 4.17 mg), quarter-dose triple combination (amlodipine 1.25 mg + losartan 12.5 mg + chlorthalidone 3.13mg), amlodipine 10mg, amlodipine 5mg, losartan 100mg, and placebo groups for 8 weeks. The primary outcome was the mean change in systolic blood pressure (SBP) from baseline to week 8.Results: The placebo-corrected SBP reductions of the half-dose, third-dose, quarter-dose combination, amlodipine 10 mg, amlodipine 5 mg and losartan 100 mg treatments were − 17.2, − 19.5, − 14.9, − 18.5, − 11.3 and − 9.9 mmHg, respectively. The BP control and response rates were significantly higher in the half-dose, third-dose, and quarter-dose combination groups than in the placebo group (all p < 0.01). Despite no intergroup differences in study drug-related adverse events, ankle circumference increased significantly in the amlodipine group compared to those in the combination treatment groups. The quarter-dose combination, amlodipine 5 mg, and losartan 100 mg groups showed similar SBP reduction and BP response rates. The SBP reduction and BP response rate in the third-dose and half-dose combination groups were not significantly different from those in the amlodipine 10 mg group but superior to those in the losartan 100 mg group.Conclusion: Low-dose triple combination therapies could be effective as antihypertensive therapies.Trial Registration: ClinicalTrials.gov identifier NCT03897868.Keywords: hypertension, blood pressure, combination therapy, low-dose, amlodipine, losartan, chlorthalidone